Post COVID health effects on patients discharged from tertiary COVID care hospital of Southern Rajasthan, India: a cross-sectional study - Das, Subhashree; Singh, Lakhan; Nadeem, Sharique; Dubey, Deepak Kumar (International Journal Of Community Medicine And Public Health, 2022)
Background: The World Health Organization declared the 2019-20 Coronavirus outbreak a public health emergency of international concern on 30th January 2020 and a pandemic on 11th March 2020. It has been creating havoc and a sense of serious insecurity and panic like situation. After recovery patient remain at risk of lung disease, heart disease, and mental health disorders. There have been long term sequelae of adverse effects. This study is being conducted as of now there is limited evidence of post-COVID sequelae as well as the initial psychological impact of COVID-19 is known and further research is required in this topic. Methods: Cross-sectional study was conducted on patients of a teaching hospital in south Rajasthan. Along with socio-demographic proforma, impact of event scale-revised (IES-R Scale) was used to collect the sociodemographic details and psychological impact on patients after they recovered from the disease. Chi-square test was used to find out statistical significance. Results: A total of 153 patients were taken for analysis. Fever followed by breathing difficulty was found to be most common post COVID physical symptoms. IES-R scale had significant associations with age group, co-morbid condition, smoking and alcohol intake. Conclusions: During the initial phase of pandemic, India presented with a high prevalence of post COVID health effects along with a psychiatric sequela. Considering this as an alarming impact, it is suggested to routinely monitor the patients even after discharge from the hospitals.